2019
DOI: 10.1186/s12871-019-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and sufentanil combination versus sufentanil alone for postoperative intravenous patient-controlled analgesia: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Previous studies have demonstrated that dexmedetomidine improves the quality of postoperative analgesia. In the present study, we performed a meta-analysis of randomized controlled trials to quantify the effect of dexmedetomidine as an adjuvant to sufentanil for postoperative patient-controlled analgesia (PCA). Methods PubMed, Embase, the Cochrane Library, and Web of Science were systematically searched for randomized controlled trials in which dexmedetomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Clinical studies have shown that sufentanil has the highest therapeutic index of all opioids [ 23 ] . As a result, sufentanil can provide stronger analgesic effects over a longer period than the same dose of fentanyl or morphine and can reduce respiratory depression and the incidence of adverse reactions [ 6 , 23 ] . Li and his team reported that administration of sufentanil could reduce emergence agitation in children receiving sevoflurane anesthesia for adenotonsillectomy compared to fentanyl, without delaying the recovery time or causing significant hypotension [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that sufentanil has the highest therapeutic index of all opioids [ 23 ] . As a result, sufentanil can provide stronger analgesic effects over a longer period than the same dose of fentanyl or morphine and can reduce respiratory depression and the incidence of adverse reactions [ 6 , 23 ] . Li and his team reported that administration of sufentanil could reduce emergence agitation in children receiving sevoflurane anesthesia for adenotonsillectomy compared to fentanyl, without delaying the recovery time or causing significant hypotension [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil has a strong analgesic capacity and sedative effect and lasts longer [ 5 ] . It has a mild effect on the cardiovascular system and no effect on histamine release, so it can effectively reduce postoperative pain in children [ 6 ] . Therefore, it is widely used in the induction and maintenance of anesthesia in pediatric cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recent studies have confirmed that DEX can be used in the perioperative period of cesarean section to assist analgesia. 13,14 There are also studies reporting the effect of DEX on improving mood. 15,16 Furthermore, it is worth mentioning that DEX can act on the locus coeruleus and thus produce a sedative effect similar to natural sleep by activating endogenous sleep pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Clonidin und Dexmedetomedin haben neben ihren antideliranten und sedierenden Eigenschaften auch eine koanalgetische Wirkung. Durch die Verwendung von Alpha-2-Agonisten verringert sich die Gefahr der opioidinduzierten Hyperalgesie [28] und es können Opioide eingespart werden [29,30]. Zu beachten ist die Gefahr der Hypotension und der Bradykardie.…”
Section: Koanalgetikaunclassified